Rare tumors of skin: malignant cutaneous adnexal tumors and clinicopathological features - SAÇAK, BÜLENT (My University, 2023)
Background: Cutaneous adnexal tumors (CATs) are a large group of neoplasms of the skin and the pathological diagnosis can be challenging. Objective: The aim of this study was to examine clinicopathological features of malignant cutaneous adnexal tumors (MCATs) and to identify therapeutic and prognostic implications. Materials and methods: Twenty-six patients diagnosed with MCATs and operated in our center were included. Demographic and clinical characteristics of patients, tumor size, histological subtype, perineural and lymphovascular invasion, re-excision status, lymph node metastasis, distant metastasis, recurrence, follow-up, and treatment choice were recorded. All lesions were excised with 1 to 2-cm surgical margin. Surgical margin was determined according to tumor size. Results: Of 26 patients, 14 were males and 12 were females (median age: 66 years). Median follow-up was 52.08 months. Tumor location was the face in 69.2% (n = 18) patients, followed by scalp and neck region. Four patients had coexisting skin tumors. Majority of MCATs (69.2%, n = 18) originated from sweat glands. Median tumor diameter was 4 (range, 0.8 to 17) cm. There was a statistically significant correlation between presence of perineural invasion and advanced disease (P = 0.036). Majority of the patients had Stage 1-2 disease, while two patients had Stage 4 disease. In six patients (23.1%), re-excision was performed due to surgical margin positivity. Conclusion: Incidence of MCATs has an increasing trend with advanced age and these tumors are more commonly seen in men and in visible sites of the body such as head and neck and scalp. Wide resection according to tumor size is the first-line treatment.
Keywords: Malignant cutaneous adnexal tumors; perineural invasion; prognostic